Visual Sensitivity in Complex Regional Pain Syndrome and Fibromyalgia: An Online Study. (March 2022) - Ten Brink, Antonia F.; Bultitude, Janet H.
Perceptual anomalies can provide insights into underlying pathologies even when they are not the main symptom of many clinical conditions. Complex regional pain syndrome (CRPS) and fibromyalgia are chronic pain conditions associated with changes in the central nervous system, possibly leading to enhanced visual sensitivity. It is unclear whether this occurs more than for people with other types of pain. We examined visual sensitivity elicited by different stimuli and in daily life, through an online study of people with CRPS ( n = 57), fibromyalgia ( n = 74), other pain ( n = 50), and no pain ( n = 89). Respondents rated changes in pain, discomfort, or distress from viewing patterns with different spatial frequencies (lower-order visual processing), and reversible figures (bistable images; higher-order visual processing). We assessed visual sensitivity in daily life using the Leiden Visual Sensitivity Scale and Visual Discomfort Scale. Respondents with CRPS or fibromyalgia reported more visual discomfort than pain-related and pain-free controls while viewing striped patterns and a circle, with no effect of spatial frequency. They reported more pain while viewing a nonreversible square, but not reversible figures (Necker Cube, Duck/Rabbit). Finally, they reported more daily visual sensitivity than pain-related and pain-free controls. Suppressing visual cortical activity might benefit people with CRPS or fibromyalgia.